Work Life Balance Among working Women and Housewives in Madhesh Province - Karn, Dipesh Kumar (Madhesh Journal of Interdisciplinary Research, 2026)
In Madhesh Province, Nepal, where sociocultural traditions, patriarchal norms, caste practices, purdah customs, child marriage, and joint family arrangements have a significant impact on women’s everyday lives, this qualitative study investigates work-life balance among working women and housewives. Through in-depth interviews, observation, and a review of secondary literature, the study investigates how women face dual loads from professional job, childcare, domestic duties, and agricultural labor. The study concludes that shared household responsibilities, supportive institutional policies, women’s education, entrepreneurship, political participation, and gender-sensitive social transformation are essential to improve women’s wellbeing and work-life balance in Madhesh Province, even though women’s autonomy and participation in education and employment have gradually increased. Government office schedules, unequal domestic labor, insufficient rest, and social expectations contribute to stress, fatigue, and health-related challenges. Stress, exhaustion, and health-related issues are exacerbated by government office schedules, unequal home work, lack of sleep, and social expectations. While joint family systems help with childcare, they can also lead to conflict between family members. The study comes to the conclusion that improving women’s well-being and work-life balance in Madhesh Province requires shared home responsibilities, supportive institutional policies, women’s education, entrepreneurship, political engagement, and gender-sensitive societal reform.